Passive RFID-based chemicals’ storage management system - Osman, Rosiah (2014)
The management of chemical inventory in laboratories is necessary for safety purpose as well as fulfilling regulatory compliance. As for academia laboratories, frequent inspections and data updating of chemicals storage are very crucial to prevent unforseen accidents to students and researchers. In most academia laboratories, management of chemicals are normally still being done manually which is very time consuming. As a result, the report data is not being updated and expired chemicals may accidentally being used. This research proposes UHF Gen2 Passive Tags Radio Frequency Identification (RFID) technology to be used in the chemical inventory management system to shorten the inventory process time. Laboratory experiments were done for chemical storage tracking on several RFID reading conditions such as various distances between the tags-reader and also orientation angle of the tags-reader. For distance less than 30 cm, the detection rate was 90% and above. The captured data was then exported to personal computer for further data processing and manipulating such as chemical tracking, quantity checking and producing alert notifications. Microsoft Excel Spreadsheet is used in recognizing the nearly expired chemicals through color code alert notice. Meanwhile, Global System for Mobile Communication (GSM) modem which provides mobile device connectivity between the database to remote application server system was connected through Open Data Base Connectivity (ODBC). JavaScript, PHP and MySQL programming languages were written to check on the expiration date of the chemicals as well as producing the alert notification status via Short Message System (SMS) in real time to the person-in-charge‟s handphone. The system was tested and the recipients received the notifications accordingly through their mobile phones which means that the result was successful. The proposed system has been implemented in chemical environment of academia laboratories only however it is applicable for other asset tracking environment for future use.